2013
DOI: 10.1038/leu.2013.226
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/Akt/mTOR signaling pathway in B-precursor acute lymphoblastic leukemia and its therapeutic potential

Abstract: B-precursor acute lymphoblastic leukemia (B-pre ALL) is a malignant disorder characterized by the abnormal proliferation of B-cell progenitors. The prognosis of B-pre ALL has improved in pediatric patients, but the outcome is much less successful in adults. Constitutive activation of the phosphatidylinositol 3-kinase (PI3K), Akt and the mammalian target of rapamycin (mTOR) (PI3K/Akt/ mTOR) network is a feature of B-pre ALL, where it strongly influences cell growth and survival. RAD001, a selective mTORC1 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 56 publications
1
90
0
1
Order By: Relevance
“…7 Studies have shown that resistance to leukemia chemotherapy is correlated with the activation of PI3K/Akt signaling pathway, as manifested by the fact that inhibition of this signaling pathway can reverse MDR and sensitize tumor cells to chemotherapeutics. [7][8][9] Peroxisome proliferator-activated receptors (PPARs) are nuclear steroid receptors that regulate diverse biological processes such as lipid and carbohydrate metabolism, development, differentiation, apoptosis, neoplastic transformation, inflammation, and regeneration. [10][11][12] PPARs form heterodimers with retinoid X receptors (RXRs) and bind to PPAR response elements (PPREs) located in the promoter of target genes to regulate transcription.…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies have shown that resistance to leukemia chemotherapy is correlated with the activation of PI3K/Akt signaling pathway, as manifested by the fact that inhibition of this signaling pathway can reverse MDR and sensitize tumor cells to chemotherapeutics. [7][8][9] Peroxisome proliferator-activated receptors (PPARs) are nuclear steroid receptors that regulate diverse biological processes such as lipid and carbohydrate metabolism, development, differentiation, apoptosis, neoplastic transformation, inflammation, and regeneration. [10][11][12] PPARs form heterodimers with retinoid X receptors (RXRs) and bind to PPAR response elements (PPREs) located in the promoter of target genes to regulate transcription.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the PI3K/AKT pathway and its potential as a therapeutic target for tumor treatment has been investigated in preclinical studies into a number of tumor types, including lung, breast and renal cancer, neuroblastoma and glioblastoma. The results of these studies indicate that the PI3K/AKT signaling pathway and those downstream of it are potential targets for therapeutic intervention (38)(39)(40)(41). The PI3K/AKT pathway serves a role in apoptosis, cell cycle progression and tumorigenesis; therefore, we hypothesize that ailanthone-induced apoptosis may also involve the PI3K/AKT pathway, demonstrating that the ailanthone treatment of Huh7 cells resulted in a decrease in the expression of PI3K and AKT phosphorylation at threonine-408 and serine-473.…”
Section: Discussionmentioning
confidence: 99%
“…Akt is a main target of PI3K and is closely related to a variety of cell biological behaviors such as metabolism regulation, cell survival and particularly apoptosis (24,25). Activation of key survival signaling molecules such as PI3K/Akt, especially increasing Akt phosphorylation levels, is not only closely related to cancer cell development and apoptosis inhibition but is also a main step leading to multidrug resistance (26,27).…”
Section: Discussionmentioning
confidence: 99%